2023
DOI: 10.3390/ijerph20043264
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle and Sport Injuries: A Systematic Review

Abstract: The presence of female athletes has only increased in recent years, as has the incidence of injuries in female sports activities. These injuries are conditioned by multiple factors, including hormonal agents. It is estimated that the menstrual cycle may be related to the predisposition to suffer an injury. However, a causal relationship has not yet been established. The aim of this study was to analyse the relationship between the menstrual cycle and injuries in female sports practice. A systematic search of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Authors like Martínez-Fortuny, N. et al observed that hormonal fluctuations throughout the MC alter variables such as laxity, strength, body temperature, and neuromuscular control, among others. This means that women are constantly adapting to hormonal variations, exposing them to a higher risk of injuries [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors like Martínez-Fortuny, N. et al observed that hormonal fluctuations throughout the MC alter variables such as laxity, strength, body temperature, and neuromuscular control, among others. This means that women are constantly adapting to hormonal variations, exposing them to a higher risk of injuries [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MC’s influence on pelvic floor musculature, including alterations in perineal musculature activity, muscle tone, strength, and contraction drive, has been documented [ 17 ]. Given the reported rise in injuries among women compared to men and their potential association with menstruation, studies have explored links between the MC and injuries [ 18 ]. Variations in strength levels, hormonal fluctuations, including elevated estrogen levels associated with improved endurance and progesterone’s impact on cardiorespiratory effort during exercise, have been observed [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These cases suggest that athletes who engage in sports activities with poor physical or mental health are more likely to be injured, which can lead to poor performance. In particular, females who participate in sports need to be cautious when they are not feeling well due to hormonal changes during their menstrual cycle, and the risk of injury increases owing to muscle relaxation, as well as strength, body temperature, and neuromuscular regulation changes [ 34 , 35 ]. This is because females have a greater risk of musculoskeletal injuries, such as patellofemoral pain syndrome and ACL injury, during menstruation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…También es necesario tener en cuenta el efecto del ciclo menstrual en las mujeres, haciendo que la cantidad de estrógeno y progesterona varíe en cada fase del ciclo. Asimismo, hay que destacar la alta incidencia de amenorrea en las deportistas de élite, influyendo igualmente en el rendimiento y en la probabilidad de sufrir algún daño estructural (Goldring et al, 2016;Martínez-Fortuny, Alonso-Calvete, Da Cuña-Carrera, Abalo-Núñez, 2023).…”
Section: Discussionunclassified